1992
DOI: 10.1159/000170038
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Fluid Loss from the Peritoneal Cavity

Abstract: During peritoneal dialysis, fluid is transported out of the peritoneal cavity by lymphatic and nonlymphatic pathways, thereby decreasing net ultrafiltration by 40-50% and reducing small solute clearance by 15-20%. The direct lymphatic pathway consists of the diaphragmatic lymphatics, which directly connect the peritoneal cavity to the bloodstream. The interstitial lymphatic and direct blood entry pathways convey fluid that has been driven into the interstitial space of the tissue surrounding the peritoneal cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The relative contribution of these two components of peritoneal absorptive flow (which both are considered to be bulk flows [19,27]) is controversial [6,7,[18][19][20]36], However, the simultaneous estimation of the peritoneal bulk absorptive flow (as estimated by Ke) and the direct lymphatic absorption (as estimated by KPP) may yield an approxi mate estimate of the order of magnitude of absorption into adjacent tissues (as absorp tion into tissue approximately should equal the difference between KP and KPP).…”
Section: Relative Importance O F Lymphatic Absorption and Absorption mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contribution of these two components of peritoneal absorptive flow (which both are considered to be bulk flows [19,27]) is controversial [6,7,[18][19][20]36], However, the simultaneous estimation of the peritoneal bulk absorptive flow (as estimated by Ke) and the direct lymphatic absorption (as estimated by KPP) may yield an approxi mate estimate of the order of magnitude of absorption into adjacent tissues (as absorp tion into tissue approximately should equal the difference between KP and KPP).…”
Section: Relative Importance O F Lymphatic Absorption and Absorption mentioning
confidence: 99%
“…However, several studies have shown that the plasma appearance rate of a macromolecular marker is on average only about 10-20% of its disappearance rate from the peritoneal dialysate (in clinically stable CAPD patients [8][9][10] as well as in animals [11][12][13][14][15]). Furthermore, studies in animals have demonstrated that a major part of the lost marker accumulates inside the tissues ad jacent to the peritoneal cavity, mainly in the liver, diaphragm and anterior abdominal wall [13,[15][16][17], The direct lymphatic and non lymphatic (convective absorption into tis sues) absorption of fluid in peritoneal dialysis has recently been reviewed [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, at the same time fluid disappears from the abdominal cavity back to the circula tion. Controversy exists whether this fluid reabsorption from the abdominal cavity dur ing a dwell with a hypertonic solution is main ly caused by absorption into the lymphatic system or by transcapillary backfiltration due to colloid-osmotic pressure within peritoneal capillaries in combination with a small lym phatic uptake of fluid [1], The basis of this controversy is the disagreement in the inter pretation of the disappearance of intraperitoneally administered macromolecular markers that are used to calculate intraperitoneal fluid kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid absorption from the peritoneal cavity is due to two separate mechanisms: (i) direct lymphatic absorption via lymphatic stomata mainly in the diaphragm, and to a lesser extent, through visceral lymphatic pathway; and (ii) fluid absorption into the peritoneal tissue interstitium, where the fluid is absorbed into the capillary due to the Starling forces, whereas the macromolecules are absorbed slowly into local lymphatics together with a fraction of the fluid (16). Fluid absorption from the peritoneal cavity adversely affects the efficacy of PD by reducing the potential for net fluid removal by 40–50%, and by reducing small solute clearances by 15–20% (17). The rate of fluid absorption has been shown to increase with time on dialysis (18).…”
Section: Discussionmentioning
confidence: 99%